ETHNIC-RACIAL RELATIONS IN PROFESSIONAL EDUCATION: THE DECOLONIZATION OF THE SCHOOL CURRICULUM AT IFMT - Mota, Alessandra Ferreira; Pereira, Daiany; Dias, Eliara Sousa; Batista, Juliete Teotônio; Vieira, Paulo Alberto dos Santos (Editora Impacto Científico, 2025)
This study, resulting from the master’s research Permanence of Black Students at IFMT/Juína Campus: The Material and the Symbolic in Affirmative Action Policy (2018–2020), reflects on the decolonization of the school curriculum in the Integrated Technical Course in Agriculture, in light of Law No. 10.639/2003. Using a qualitative approach and Bardin’s Content Analysis Technique, the Institutional Development Plan (2014–2018) and the Pedagogical Course Project (2015) were examined. The results reveal a superficial treatment of the ethnic-racial theme, with the absence of concrete pedagogical actions and curricular transversality. It is concluded that curriculum decolonization requires a rupture with Eurocentric logic, effective incorporation of Afro-Brazilian knowledge, continuous professional training, and institutional policies aimed at racial equity.DOI: https://doi.org/10.56238/edimpacto2025.083-006